Hubungan antara Sajian Informasi Klarifikasi Program Recycle Station dengan Sikap Netizen terhadap Sociolla - Budiman, Ratu Marshyarina Ridzkan; Bakti, Iriana; Zubair, Feliza (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aimed to determine the relationship between the presentation of clarification information about the Recycle Station program on the Instagram account @mamaserbabisa and netizens' attitudes toward Sociolla. The study tested the information integration theory to understand the extent of the relationship between the valence and weight of the clarification information about the Recycle Station program and netizens' cognitive, affective, and conative attitudes toward Sociolla. This research used a quantitative method with a correlational approach and Spearman Rank correlation test. Data collection techniques included questionnaires and literature studies from books, online journals, and other secondary references. The respondents of this study were 98 accounts that liked the post about the Recycle Station program on the Instagram account @mamaserbabisa, selected through simple random sampling. The results of this study showed that the presentation of clarification information about the Recycle Station program had a strong and significant relationship with netizens' attitudes.